Pengaruh Pengalaman dan Nilai Pelanggan Terhadap Loyalitas Melalui Kepuasan Sebagai Variabel Intervening pada Pelanggan Scarlett Whitening di Kota Makassar - Kurniah, Kurniah; Awaluddin, (Study of Scientific and Behavioral Management, 2022)
ABSTRACT This study aims to determine the effect of customer experience and value on loyalty through satisfaction as an intervening variable for Scarlett Whitening customers in Makassar City. The population sample is 96 people to facilitate facial calculations. Researchers obtained a sample of 100 respondents. The data analysis technique in this study is using structural Equation Modeling (SEM) using the help of SmartPLS version 3.0 for windows. The results of this study indicate that customer experience does not have a positive effect on customer loyalty, customer value has a positive effect on customer loyalty, customer experience has a positive effect on customer satisfaction, customer value has a positive effect on customer satisfaction, customer satisfaction has a positive effect on customer loyalty, customer experience has a positive effect on customer satisfaction through customer loyalty as an intervening variable, and customer value has a positive effect on customer satisfaction through customer loyalty as an intervening variable. Keywords : experience, customer value, satisfaction, customer loyalty